Thrifter: An online marketplace with a recommender system - Ari Freyr Ásgeirsson 1990-; Ívar Oddsson 1990-; Sigursteinn Bjarni Húbertsson 1990-; Valgeir Björnsson 1989-; Ævar Ísak Ástþórsson 1990- (2015)
Online marketplaces in Iceland offer limited help when it comes to creating advertisements with a standardized look and feel or finding things that users are interested in. Thrifter is a marketplace system designed with the user in mind by both helping with the ad creation process and by recommending items based on recent user history. In this report we outline the design of the Thrifter platform and how the development was undertaken during the course of the final project. Rannsóknarskýrslu og önnur fylgiskjöl er að finna í Thrifter, skýrslur.zip.